PENGARUH PROJECT BASED LEARNING BERDIFERENSIASI BERBASIS KEARIFAN LOKAL TERHADAP PRESTASI BELAJAR GEOGRAFI PESERTA DIDIK SMA - Nisa Salma Kamila; Esti Sarjanti; Suwarno Suwarno (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
This research is motivated by the suboptimal implementation of learning that accommodates the diversity of student characteristics and integrates local wisdom in geography learning. This study aims to analyze the effect of the differentiated Project Based Learning (PjBL) model based on local wisdom on the geography learning achievement of class X students of SMA Negeri 1 Purwokerto on hydrology material. The study used a quasi-experimental method with a Nonequivalent Control Group Design. The research sample consisted of 30 students selected through matching techniques based on initial abilities so that 15 pairs of students were obtained in the experimental class and the control class. Data were analyzed using descriptive statistics, prerequisite tests, Independent Samples t-test, and Mann-Whitney U Test. The results showed that the learning achievement of students in the experimental class was higher than the control class with a mean rank of 20.73 and 10.27, respectively. The results of the Mann-Whitney U test showed an Asymp. Sig. (2-tailed) value of 0.001 (p<0.05), which indicated a significant difference in learning achievement between the two groups. These findings indicate that the implementation of a differentiated, local wisdom-based PjBL model has a positive impact on geography learning achievement. This model has the potential to be a learning alternative that supports the implementation of the Independent Curriculum through student-centered and contextual learning appropriate to the local cultural environment.